Perancangan Prototype Antarmuka Sistem Informasi Simpan Pinjam Pada Koperasi Wanita Tutur Mandiri Desa Sooko Menggunakan Metode Human Centered Design (HCD) - Civica Moehaimin Dhewanty; Satrio Hadi Wijoyo; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Tutur Mandiri Women's Cooperative has a savings and loan service unit that deals with all savings and loan matters carried out by Tutur Mandiri Women's Cooperative members. Until now, Tutur Mandiri Women's Cooperative has only carried out manual records related to data on cooperative members, including data on savings and loans. This can lead to errors or data loss. Tutur Mandiri Women's Cooperative has also been going to implement a system but the information system has not been implemented. The reason is that administrators and supervisors find it difficult for doctors, too complex and not following the needs and desires of the cooperative. So the cooperative management needs a prototype that is used for recording data on savings and loans. To be able to produce a prototype, it is necessary to carry out the process of designing an information system interface. Based on these problems, research was carried out on the design of an information system interface prototype using the Human-Centered Design (HCD) method which later can provide an introduction, explanation, and initial description of how the management of a cooperative organization of savings and loan data. This research was conducted by conducting literacy studies, planning the Human-Centered Design (HCD) process, determining the context of use, specifying the needs and requirements of users and organizations, designing solutions and prototypes, evaluating solutions and prototypes, and improving the design of solutions and prototypes.